Recent Finding in Astrononmy Point to Turbulence and Strong Magnetic Fields (Correct Prediction of Black-Hole Shape) (Global Journal of Science Frontier Research, 2019)
The author predicted that the Black Holes must have hyperboloid shape and shortly after the prediction a Black Hole was observed with high resolution and photographed -it had hyperboloid shape. How these kinds of predictions are done is subject to another published article. The author further explained that two galaxies (or two Black Holes) would merge only if they have opposite magnetic polarity, which means they spin in opposite directions. Indeed, old stars were found in the Milky Way, which span in opposite direction, remnants of an old galaxy swallowed 10 billion years ago. This means that the Black Holes and galaxies at the first half of their lifespan (during their active period) spin counterclockwise (like anti-vortices) and produce matter (new stars, which move away from the Black Hole). In the second half of their lifespan, they must spin clockwise (like vortices) to attract and swallow the old stars, thus recycling them. The old stars need to be recycled so that new stars can be created in perfect order. This means that the Universe cannot expand forever -the process of expansion must be followed by a process of contraction. This article explains that all observed merging of Black Holes, galaxies, and galaxy clusters requires opposite magnetic polarities of the mergers. Since the younger ones spin counterclockwise and expand, while the older ones spin clockwise and contacts, the merging is a process of recycling of the old.
Keywords: : turbulence in cosmos; merging of Black Holes; merging of galaxies; merging of galaxy clusters; magnetic origin of the merging